2008
DOI: 10.1590/s0101-20612008000500024
|View full text |Cite
|
Sign up to set email alerts
|

Composição química e rendimento da carne ovina in natura e assada

Abstract: A ovinocultura de corte no Brasil está em franca expansão, em virtude do aumento do consumo da carne desta espécie animal e também pela oferta de carne ser menor que a demanda do mercado interno, o que causa a valorização do produto. Isso torna a criação destes animais economicamente mais rentável em relação às demais espécies produtoras de carne para consumo humano.Grande parte das carnes e de produtos cárneos consumidos atualmente pelo homem passa por algum tipo de tratamento térmico, por ser mais palatável … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 11 publications
2
4
1
3
Order By: Relevance
“…There was inferiority in the average values observed in this study for losses by cooking (31.26%) and evaporation (13.57%) and superiority for dripping fat loss (8.57%) when compared with those values observed by Pinheiro et al (2008). These authors found average values of 35.20% for cooking loss, 33.84% for evaporation loss, and 1.36% for fat drip loss when they rated the meat quality of one half Ile de France and one half Santa Inês lamb.…”
Section: Discussioncontrasting
confidence: 80%
“…There was inferiority in the average values observed in this study for losses by cooking (31.26%) and evaporation (13.57%) and superiority for dripping fat loss (8.57%) when compared with those values observed by Pinheiro et al (2008). These authors found average values of 35.20% for cooking loss, 33.84% for evaporation loss, and 1.36% for fat drip loss when they rated the meat quality of one half Ile de France and one half Santa Inês lamb.…”
Section: Discussioncontrasting
confidence: 80%
“…Almeida (2011) also concluded that the addition of 4.0% oatmeal, favored lower weight loss by cooking (18.4%) in relation to the control group. These results are similar to those reported by Pinheiro et al (2008).…”
Section: Product Yieldsupporting
confidence: 93%
“…Similar values to those presented here were reported by Dias et al (2002), who recorded 76.54 g/100 g, 1.08 g/100 g, 2.06 g/100 g and 23.27 g/100 g for moisture, ash, lipid and protein levels, respectively, when examining the physical and physicochemical characteristics of culled Moxotó chevon, as well as those reported by Duarte (2003), who recorded values of 75.13 g/100 g, 22.69 g/100 g, 2.55 g/100 g and 0.98 g/100 g for moisture, protein, fat and ash levels, respectively, when analyzing shoulder cuts from crossbred Boer goats slaughtered at 228 days. Pinheiro et al (2008) found values of 74.05 g/100 g moisture, 5.36 g/100 g fat, 18.85 g/100 g proteins and 1.15 g/100 g ash in a study of the chemical composition and yield of mutton in natura, which is consistent with the results shown for the meat physicochemical characteristics. Different values were reported by Santos Júnior et al (2009), who recorded values of 76 g/100 g moisture, 19.18 g/100 g protein, 5.40 g/100 g lipids, 1.18 g/100 g ash and 5.56 pH in a study of the physicochemical characteristics of culled mutton used to prepare hamburgers supplemented with oat flour.…”
Section: Meat Characteristicssupporting
confidence: 88%